New wine in old bottles? An analysis of communication research trends focusing on media - So-Eun Lee; Seongcheol Kim (International Telecommunications Society (ITS), 2018)
Media technologies have evolved over time, competing with one another. Media are socially important agents rather than mere technological objects as they penetrate deeply into people's lives. For example, TV has been leading the mass communication age for a long time since the emergence of electronic media. Computers are multimedia devices that have led to the era of convergence by flattening different content modalities. The proliferation of mobile media brings the revolutionary changes, hastening the advent of the personal communication age. And most recently, new technologies such as wearable devices are creating unprecedented forms of communication. The transition of the major media devices leads to the fundamental sociocultural changes, which can be called 'paradigm shifts'. Then, has the paradigm of media research changed to reflect this technological and social transition? Has there been progression of research theories or methodologies that corresponds to the conversion of major media? If so, in what context? If not, why? This study aims to answer these questions through a review of more than 30 years of communication research published in the Journal of Broadcasting & Electronic Media (JOBEM).
Keywords: 330